Pengaruh Green Marketing Terhadap Minat Beli Konsumen: Systematic literature reviews - Ramdhan Kurniawan; Faridah Iriani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose of writing this paper is to determine the effect of green marketing on consumer buying interest. This research is a literature study that focuses on the topic of the influence of Green Marketing on consumer buying interest, with inclusion criteria: publications in journals, 2013-2023 year range. The data was taken through Google Scholar and analyzed using the comparative method. The result of this work is that green marketing has an important role in encouraging companies to adopt environmental issues in marketing strategies to increase consumer buying interest. The effect varies depending on contextual factors such as location, industry, and market conditions. In an era where consumers' environmental awareness is getting higher, a green marketing strategy must be comprehensive, including aspects of product quality, price, distribution, promotion, and corporate social responsibility. Increased consumer knowledge about the benefits of green marketing can influence purchase intention and purchasing decisions, and companies need to educate consumers about environmentally friendly products and meet their expectations regarding price and product quality.